Solar-wind/magnetosphere coupling: Understand uncertainties in upstream conditions - Di Matteo, Simone; Sivadas, Nithin (Frontiers in Astronomy and Space Sciences, 2022)
Many studies of solar-wind coupling with the magnetosphere depend on the properties of the solar wind impacting the magnetosphere. Our ability to estimate these properties relies heavily on spacecraft measurements at the first Lagrangian point (L1), far upstream of the Earth. Our best estimates of these are made by time-shifting the observations to the bow shock nose. Hence, we are uncertain of the solar wind parameters that affect the magnetosphere. Apart from instrumental errors, the uncertainty stems from many simplifying assumptions that ignore the inherent variability of the solar wind at L1 (e. g., solar wind meso-scale structures, transverse gradients) as well as physical processes downstream (e. g., the effect of the foreshock, structured bowshock, magnetosheath plasma, variable solar wind propagation). These uncertainties can lead us to significantly misinterpret the magnetosphere and ionosphere response, adding avoidable research time and expense. While multi-spacecraft missions can reduce uncertainty by gradually filling our knowledge gaps, there will always be a certain degree of uncertainty in determining relevant solar wind parameters that impact the magnetosphere. Estimating this uncertainty and correcting for them in our studies is crucial to the advancement of our field and, in particular, (i) our understanding of the solar-wind/magnetosphere coupling, (ii) global magnetospheric simulations, and (iii) space weather forecasting. In the next decade, paired with novel multi-spacecraft missions, we make a case for placing financial and organizational resources to support quantifying, understanding and correcting for uncertainties in upstream solar wind conditions.